Association Between Cigarette Smoking and Multiple Sclerosis - Sri Lestari, Sri Lestari; Rusdi, Rusdi (The International Journal of Medical Science and Health Research, 2024)
Background: The association between cigarette smoking and multiple sclerosis (MS) has garnered significant attention in the literature, with numerous studies elucidating the intricate relationships between tobacco exposure and MS risk, progression, and health outcomes. The exploration of these relationships has evolved over the years, revealing both the direct and indirect effects of smoking on the disease. Literature Review: The literature on the association between cigarette smoking and multiple sclerosis (MS) has revealed a complex interplay between environmental and genetic factors that significantly influence the disease's risk and progression. The studies reviewed consistently highlight smoking as a critical modifiable risk factor for MS, with evidence suggesting that both active smoking and exposure to environmental tobacco smoke (ETS) contribute to increased susceptibility and exacerbation of the disease. Conclusion: Overall, the literature consistently underscores the multifaceted role of cigarette smoking in MS, revealing that both direct and indirect exposures significantly impact disease risk and progression. The interaction between smoking and genetic predispositions, particularly concerning specific HLA genes, further complicates the understanding of MS etiology. These findings call for more focused research on smoking behaviors in MS patients and the development of tailored smoking cessation interventions to improve health outcomes for this population.